Shrinkage Compensation Technology of Concrete Filled Steel Tubular Structure of Large Cross-Sea Bridge - Yi Zhao; Xiao Wu (Advances in Civil Engineering, 2023)
In view of the poor accuracy and unsatisfactory effect of shrinkage compensation for concrete-filled steel tubular structures of large cross-sea bridge (CSTS-LCSB), a new shrinkage compensation technology for CSTS-LCSB is proposed. The shrinkage mechanism of CSTS-LCSB is analyzed, including plastic shrinkage, dry shrinkage, autogenous shrinkage, and carbonation shrinkage. The proportion of dry shrinkage and autogenous shrinkage in ordinary concrete and high-strength concrete is determined. The CSTS-LCSB has different shrinkage forms in different environments, and the shrinkage strain state of CSTS-LCSB in different environments is calculated according to the difference. The shrinkage area of the concrete structure is determined, and the expansion agent is used to compensate for the shrinkage area of CSTS-LCSB. The experimental results show that the proposed compensation technology has a good effect on shrinkage compensation and has certain feasibility.